Pengembangan Media Flash Card Berbasis Microsoft Powerpoint pada Keterampilan Membaca Nyaring Kelas II SD - Rahmadita Putri Rusmawandani; Ikha Listyarini; Ryky Mandar Sary (STKIP Andi Matappa Pangkep, 2023)
The purpose of this study was to develop Microsoft PowerPoint-based flash card media for reading aloud skills of second grade students in elementary schools that met valid and feasible criteria. In this study using the Research and Development (R&D) method of the ADDIE model which consists of five steps namely Analysis, Design, Development, Implementation, Evaluation with descriptive data analysis techniques. The media validation results reached 97% in the